Ocular toxicity following carboplatin chemotherapy for neuroendocrine tumour of the bladder. (April 2023) - Ng, Jia; Sadiq, Muhayman; Mansoor, Qasim
Introduction: Carboplatin is a commonly used platinum analogue chemotherapeutic agent that is similar to cisplatin but is known to be better tolerated. This case report outlines a case of ocular toxicity following carboplatin chemotherapy used for the management of a neuroendocrine tumour of the bladder. Case report: A 70-year-old man with a history of neuroendocrine bladder cancer underwent chemotherapy with carboplatin and etoposide. He presented 4 weeks following his fourth chemotherapy cycle with a 1-week history of right eye blurriness. The patient had suffered a similar episode 2 weeks following his third chemotherapy cycle in his left eye. Carboplatin-induced ocular toxicity was suspected and his vision remained stable following cessation of carboplatin chemotherapy. Discussion: Current literature on carboplatin-induced ocular toxicity remains scanty, however, previous cases have reported symptoms beginning 5 days to 2 weeks following carboplatin use. Visual disturbance in the form of altered colour vision, blind spot, blurred vision and metamorphopsia have been reported by previous literature. This case report emphasised a case of bilateral sequential blurring of vision following carboplatin chemotherapy. Conclusion: It remains critical for ophthalmologists and oncologists to look out for ocular side effects of chemotherapy due to its devastating effects.